Le@d 3.0 - Barroca, Ana; Neto, Catarina (Conferência - Investigação e Intervenção em Recursos Humanos, 2016)
Le@d3.0 Academy is a project supported by the ERASMUS+ Programme aiming at creating a Knowledge Alliance between Academy and Industry to widespread the use of MOOCs/ Open Educational Resources (OERs) by trainers to develop the soft e-leadership skills required by the labour market in the digital age. During the research phase, 9 partners from 7 EU countries have developed efforts to better understand the: i. Which are the main skills that a Leader must act in order to be effectively driving the change, innovating societal practices, establishing new business model, helping to attract, develop and manage talents (thus being a E-Leader)? ii. Which are the main skill gaps that managers, today and to be (students) show/declare, that need to be filled up? iii. Can these skills be trained anchoring learning processes to web based tools and technologies? Which are the most effective technology based solutions for training e-leadership skills? And which are the main issues underpinning the design of effective teaching strategies and process? iv. Are trainers/teachers prepared to run this training? Have they already embedded these skills in their training programs? The research activities focused in 6 skill clusters: Digital basic skills, e-communication / team working / entrepreneurship & innovation / reputation / lifelong learning and involved 3 target groups: Students, Managers, Trainers reaching more than 1800 people in 6 countries. The Research Reports distils the main insights coming from the research and need analysis results, with a specific focus on one hand on the theoretical side, namely the new e-leadership paradigm and related soft skill set according to labour market needs.